Jonathan Edwards and the church - Bezzant, Rhys S. (Oxford ; New York : Oxford University Press, 2014)
"Though Edwards spent most of his life working in local churches, and saw himself primarily as a pastor, his own views on the theology of the church have never been explored in depth. This book presents Edwards's views on ecclesiology by tracking the development of his convictions during the course of his tumultuous career. Drawing on Reformation foundations and the Puritan background of his ministry, Edwards refreshes our understanding of the church by connecting it to a nuanced interpretation of revival, allowing a dynamic view of the place of church in history and new thinking about its institutional structure."--Dust jacket
Puritan search for ecclesiological order -- Ordered ecclesiological thoughts (1703-1734) -- Ordered ecclesiological passions (1735-1746) -- Ordered ecclesiological visions (1747-1758) -- Ordered ecclesiological life -- Conclusion: Orderly but not ordinary: Edwards's evangelical ecclesiology.
Includes bibliographical references (pages 261-285) and index.
Keywords: Edwards, Jonathan, -- 1703-1758.; Church -- History of doctrines -- 18th century; Edwards, Jonathan, -- 1703-1758.